Resenha - FAZENDA, Ivani Catarina A. (org.). O que é interdisciplinaridade? São Paulo: Cortez, 2008. - Nali Rosa Silva Ferreira (Centro Universitário de Belo Horizonte, 2009)
eoi/doi Deposit Form - Electronic Object Identifier http://eoi.citefactor.org/10.11248/ehum.v2i1.387